Identifikasi Modal Sosial dan Kebudayaan Masyarakat dalam Mendukung Pengembangan Perkotaan Tempeh, Kabupaten Lumajang - Afifah, Salma Aulia Nur; Naufaldy, Muhamad Zaky; Saputra, Bagus Dwi; Hutabarat, Degihon Daud Martua; Desderius, Kevie (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2025)
The identification of social and cultural capital is an attraction of Tempeh Urban which is able to help the development of Tempeh Urban by showing some of the culture or habits of the surrounding community. For the social and cultural capital of the Tempeh Urban Community, there is no need for coercion, because they carry out these activities voluntarily and culture can be created among them because of a custom. Therefore, this research helps to identify the social and cultural capital of the community in supporting the development of Tempeh Urban. This study uses a descriptive method. The type of research used is qualitative research. The data collection techniques used in this study are divided into three types, namely primary and secondary observation, conducting interviews and reading literature studies. The Tempeh Urban Community has a distinctive culture and different social capital such as the culture of lighting fireworks when there is Adam and Eve proposing during the day, then there are several villages that have different customs but still understand each other because they are a mixture of Madurese and Javanese customs. The purpose of this research is to support the development of Tempeh Urban by identifying the social and cultural capital of the community.